Ancient Israel in Sinai : the evidence for the authenticity of the wilderness tradition - Hoffmeier, James Karl, 1951- (New York, Oxford University Press, 2005)
"As director of the North Sinai Archaeological Project, James K. Hoffmeier has led several excavations that have uncovered important new evidence supporting the wilderness narratives, including a major New Kingdom fort at Tell el-Borg that was occupied during the Israelite exodus. Hoffmeier employs these archaeological findings to shed new light on the route of the exodus from Egypt. He also investigates the location of Mount Sinai and offers a rebuttal to those who have sought to locate it in northern Arabia and not on the Sinai Peninsula as traditionally thought. Hoffmeier addresses how and when the Israelites could have lived in Sinai, as well as whether it would have been possible for Moses to write down the law received at Mount Sinai. Building on new evidence for the Israelite sojourn in Egypt, Hoffmeier explores the Egyptian influence on the wilderness tradition."--BOOK JACKET.
The wilderness traditions -- The wilderness traditions and the historian of religion -- Sinai : the great and terrible wilderness -- The geography of the Exodus : Ramesses to the sea -- The location of the Re(e)d Sea -- The mountain of God -- From Egypt to Mt. Sinai : traveling and living in the wilderness -- The Sinai legislation -- Israel's desert sanctuary -- Egyptian personal names and other Egyptian elements in the Exodus-wilderness narratives -- The wilderness tradition and the origin of Israel.
Includes bibliographical references (p. [251]-323) and index.
Keywords: Bible. -- Criticism, interpretation, etc; Bible. -- Evidences, authority, etc; Bible. -- History of Biblical events; Bible. -- Geography; Sinai (Egypt) -- Antiquities